Soil quality evaluation of no-tillage reseeding grassland based on quality index area and sensitivity-resistance method - Xiaoqing Qiu; Shuang Yan; Hao Shi; Fei Xia; Wei Wei; Yu Zhang; Jiarui Ding; Jiayu Cao; Haoyang Wu; Linling Ran; Jinglong Wang; Junqiang Wang (Applied Soil Ecology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Decoding the molecular complexity of coal: A machine learning framework for component classification and solvent selection - Yu-Ying Zhou; Xing Fan; Jin-Xi Wu; Zhen-Yu Gao; Ran-Ran Hou; Chao Feng; Zhong-Qiu Liu; Qing Liu; Xiao-Yu Dong; Peng Liang (Fuel, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Post-heat treatment and pectin addition affect protein digestion and absorption release kinetics in pigs through microstructural and rheological modifications - Xiyu Qin; Xiuying Wu; Caiziyu Yu; Yi Chai; Xiaoxue Liu; Xiaoxu Zhang; Huifang Cai; Mengxuan Lai; Lili Qiu; Yanling Hao; Ran Wang; Yixuan Li; et al. (Food Chemistry, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

Potential role of dietary whole grains in Alzheimer's disease: bioactive components, mechanistic insights, and epidemiological evidence - Meng Shen; Xinru Yu; Suyang Wu; Ju Qiu; Ran Wang; Kai Li; Qian Zhang (Trends in Food Science & Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Whey protein-structured oleogels: Effect of α-lactalbumin addition and ultrasonication treatment on oleogelation - Qiu-Ya Ji; Ran Feng; Yu-Nong Chen; Chao Zhang; Jiao Wu; Meng-Jie Yu; Bao Zhang (Food Chemistry, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

To collaborate or not? Network evolutionary game-based analysis of inter-governmental behaviors for green governance of urban carbon reduction in the Yangtze River Delta region - Ran Qiu; Ziyuan Zhang; Linyu Wang; Liying Yu (Environment, Development and Sustainability, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Dual-ion permeation Janus membrane-assisted element reconstitution system enables fluorosilicate-oriented recovery from fluoride-rich and silica-rich wastewaters - Yangbo Qiu; Chao Wang; Ran Li; Lidong Feng; Shuaijun Yu; Jiangnan Shen; Long-Fei Ren; Jiahui Shao (Water Research, 2025)

Half substitution of mineral N with fish protein hydrolysate enhancing microbial residue C and N storage and climate benefits under high straw residue return - Jia Lin Wang; Xin Yu Liu; Pei Kun Jiang; Qiu Ran Yu; Qiu Fang Xu (Journal of Environmental Management, 2024)

Unveiling preferred chemoattractants for rhizosphere PGPR colonization by molecular docking and molecular dynamics simulations - Ran Chai; Fuxin Li; Yuqian Gao; Dehai Liu; Di Shang; Yanqing Yang; Jiayang Yu; Chenxiao Zhou; Yanan Li; Andong Song; Liyou Qiu (Computers and Electronics in Agriculture, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

High efficiency Hg(II) electrochemical detection based on the number of defect engineering on MoS2: Insight in synergistic action of sulfur vacancies and undercoordinated Mo - Qiu-Yu Wang; Hao-Ran Li; Huan Xu; Jia-Mei Tao; Shan-Shan Li (Analytica Chimica Acta, 2024)

A novel fluorescence platform for specific detection of tetracycline antibiotics based on [MQDA-Eu3+] system - Jia-Mei Ran; Liu Yang; Chun-Tong Liu; Qiu-Huan Liu; Yu-Long Liu; Shi-Jie Li; Ying Fu; Fei Ye (Science of The Total Environment, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Advancing immunotherapy in triple negative breast Cancer: A novel multimodal theranostic nanoplatform integrating synergetic ferroptosis and photothermal therapy - Long Cheng; Yibo Qiu; Lingyun He; Haiyang Wang; Min Zheng; Ruoyao Wang; Yaqin Hu; Huilin Yu; Wenpei Luo; Yuanyou Xia; Yang Cao; Zhigang Wang; et al. (Chemical Engineering Journal, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Solidarity or self-interest? Carbon footprint pressure measurement and spatial correlation in the Yangtze River Delta region - Ran Qiu; Liying Yu (Journal of Cleaner Production, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Identification of de novo Mutations in the Chinese Autism Spectrum Disorder Cohort via Whole-Exome Sequencing Unveils Brain Regions Implicated in Autism - Bo Yuan; Mengdi Wang; Xinran Wu; Peipei Cheng; Ran Zhang; Ran Zhang; Shunying Yu; Jie Zhang; Yasong Du; Xiaoqun Wang; Zilong Qiu (Neuroscience Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

The influence of various microplastics on PBDEs contaminated soil remediation by nZVI and sulfide-nZVI: Impedance, electron-accepting/-donating capacity and aging - Xiaoxuan Zhang; Ran Chen; Zhenhui Li; Junxia Yu; Jinyi Chen; Yuanyuan Zhang; Jinhong Chen; Qianqian Yu; Xinhong Qiu (Science of The Total Environment, 2023)

Cultivation of Haematococcus pluvialis in source-separated urine for biomass production and astaxanthin accumulation - Guan-qiu Ma; Li-hua Li; Yu Hong; Ming-ran Yu (Algal Research, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Testing the isotopic equilibrium fractionation on active speleothem based on cave monitoring - Yang-Yang Huang; Ting-Yong Li; Chao-Jun Chen; Ran Huang; Tao Wang; Yao Wu; Si-Ya Xiao; Yu-Zhen Xu; Hai-Ying Qiu; Yan Yang; Jun-Yun Li (Journal of Earth System Science, 2022)

A methodology to determine the optimal quadrat size for desert vegetation surveying based on unmanned aerial vehicle (UAV) RGB photography - Mengyu Hao; Wenli Zhao; Longjun Qin; Peng Mao; Xu Qiu; Lijie Xu; Yu Jiu Xiong; Yili Ran; GuoYu Qiu (International Journal of Remote Sensing, 2021)

De Novo and Inherited SETD1A Variants in Early-onset Epilepsy - Xiuya Yu; Lin Yang; Jin Li; Wanxing Li; Dongzhi Li; Ran Wang; Kai Wu; Wenhao Chen; Yi Zhang; Zilong Qiu; Wenhao Zhou (Neuroscience Bulletin, 2019)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Subliminal trauma reminders impact neural processing of cognitive control in adults with developmental earthquake trauma: a preliminary report - Xue Du; Yu Li; Qian Ran; Pilyoung Kim; Barbara L. Ganzel; GuangSheng Liang; Lei Hao; Qinglin Zhang; Huaqing Meng; Jiang Qiu (Experimental Brain Research, 2016)

Mitochondrial Dysfunction Induced by Honokiol - Jia-Xin Dong; Guang-Yuan Zhao; Qiu-Li-Yang Yu; Ran Li; Lian Yuan; Jing Chen; Yi Liu (The Journal of Membrane Biology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Chemical composition and antioxidant activity of the essential oil of endemic Viola tianshanica - Jin Yang; Zhen Qu; Yu-Ling Xiao; Guo-Fu Qiu; Tao Zhang; Zhong-Yuan Wu; Xian-Ran He; Xian-Ming Hu (Natural Product Research, 2011)